Oral focal mucinosis of the palate: a rare disease entity. Issue 3 (10th March 2020) - Cameron, Alice; Webster, James Edward Noctun; Wicks, Catherine Elizabeth; Colbert, Serryth Dominic
Abstract : Oral focal mucinosis (OFM) is an extremely rare, benign oral soft tissue condition; less than 10 documented cases have been reported in the literature in patients under 18 years old. OFM has an unknown aetiology and predominantly presents in the fourth and fifth decades. The pathogenesis of OFM may be due to fibroblast overproduction of hyaluronic acid. Clinically, it remains almost impossible to diagnose definitively, due to its lack of pathognomonic features, therefore such lesions may have multiple differential diagnoses and histological analysis is essential to confirm OFM. We present an unusual presentation of OFM in a 14-year-old female patient. Following excision, focal myxoid degeneration of the connective tissue was apparent. This case highlights this rare condition for consideration in differential diagnosis of clinically similar lesions.